Digital Transformation in SMEs Emerging Technological Tools and Technologies for Enhancing the SME's Strategies and Outcomes - Bhuiyan, Mohammad Rakibul Islam; Faraji, Mahfujur Rahman; Rashid, Maksuda; Bhuyan, Md Khokan; Hossain, Rashed; Ghose, Provakar (Journal of Ecohumanism, 2024)
This study aims to conduct a comprehensive analysis of digital transformation which involves the integration of digital technology into all sectors of SMEs, resulting in increased efficiency and enhanced customer service, enables SMEs to reduce overall expenditure by optimizing operational and marketing costs, thereby allowing to focus on value-adding activities, supports SMEs' technology innovation development models and strategies for fostering technological innovation within SMEs. The research identifies the difficulties encountered by SMEs during the implementation of digital transformation initiatives. Additionally, it seeks to acknowledge emerging trends in digital transformation that may affect SMEs and offer advice on proactively embracing technological advancements to sustain competitiveness. This is a mixed-method research project utilizing systematic review and deductive methods to gather qualitative data.Top of FormBottom of Form SMEs currently employing digital transformation were purposefully selected based on criteria such as authorship, publication date, sample size, and variables for this study. Furthermore, this research involved conducting thorough interviews and observations to delve into the technological innovations pursued by the participants. It was found that there are some factors of digital transformation in SMEs' technology innovation: Enhanced Operational Efficiency, Improved Customer Engagement, Global Market Access, Data driven decision making. Hence, Digital transformation in SMEs contribute autonomously to the expenses of technological innovation to foster business sustainability. This necessitates a strategic focus on enhancing consumer services and fostering a favorable attitude toward innovation in SMEs' business practices and development through technology. This study examines obstacles to SME technology innovation in production, business models, technology adoption, and strategic approaches, without analyzing costs related to SME-driven digital transformation. Future studies could investigate obstacles across various SME sectors to enhance digital tools, underscore the significance of SMEs adopting technology, integrating strategic supply chain management, and broadening their business strategies to attain sustainable development.